PENGARUH SOLVABILITAS, DAN LIKUIDITAS TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2018 - 2021 - Nuriyadi, Anggia; Bayu Kurniawan; Rita Meiriyanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
In this modern era, almost all aspects of life have undergone modernization, including market capital. The current capital market has provided a new alternative for investors. Now, investment is not only limited to real accounts and deposits in the banking system, but investment in capital markets has also developed. One of the most popular is stock. The purpose of this study is to determine the direct and indirect effect of solvency and liquidity ratios on stock returns with profitability ratios as the intervention variable. The method used in this research consists of quantitative data. Based on the research, there is no influence between the solvency ratio (X1) on stock returns (Y), which is seen partially by the t value of -0.654 and the significance value is 0.514. There is no influence between the liquidity ratio (X2) on stock returns (Y) which is seen partially by the t-value of 0.714 and the significance value of 0.477. There is no influence between the profitability ratio (Z) on stock returns (Y) which is seen partially by the t value of -0.449 and the significance value is 0.654. There is an influence between the solvency ratio (X1) on profitability (Z) which is seen partially by the t value of -2.758 and the significance value is 0.007. there is no influence between the liquidity ratio (X2) on stock returns (Y) which is seen partially by the t-value of -0.821 and the significance value is 0.414.